Literature Review: pola makan dan kualitas diet pada remaja dan dewasa dengan HIV/AIDS - Shella Putri Ferari; Siti Rahayu Nadhiroh (Poltekkes Kemenkes Aceh, 2023)
Background: Human Immunodeficiency Virus (HIV) infection remains an unresolved health problem in Brazil. Diet plays an important role in the immune system of HIV/AIDS patients because adequate amounts of macronutrients and micronutrients are important. Food quality has also been used as a proxy for predicting the risk of death and chronic diseases. Measuring diet quality is an indicator that can describe a person's dietary practices in accordance with the dietary recommendations set out to be able to live healthily.Objective: This study aimed to analyze the dietary patterns and diet quality of adolescents and adults with HIV/AIDS.Methods: This study was a systematic literature review. The protocol used in the systematic literature review of this study used the PRISMA method. The SLR protocol and evaluation were performed using the PRISMA method to select research articles that had been found. The PRISMA method collects articles from PubMed, Google Scholar, Research Gate, SINTA, Garuda, and Scopus databases. The search terms used were Indonesian and English. The search terms used in Indonesian were